Frequency, Cost, and Risk Factors of Readmissions Among Severe Sepsis Survivors*. Issue 4 (April 2015) - Goodwin, Andrew J.; Rice, David A.; Simpson, Kit N.; Ford, Dee W.
<x xml:space="preserve">Abstract</x> Objective: To determine the frequency, mortality, cost, and risk factors associated with readmission after index hospitalization with severe sepsis. Design: Observational cohort study of Healthcare Cost and Utilization Project data. Setting: All nonfederal hospitals in three U.S. states. Patients: Severe sepsis survivors (n = 43, 452) in the first two quarters of 2011. Interventions None. Measurements and Main Results: We measured readmission rates and the associated cost and mortality of readmissions in severe sepsis survivors. We used multivariable logistic regression to identify patient and hospitalization characteristics associated with readmission. Of 43, 452 sepsis survivors, 26% required readmission within 30 days and 48% within 180 days. The cumulative mortality rate of sepsis survivors attributed to readmissions was 8%, and the estimated cost was over $1.1 billion. Among survivors, 25% required multiple readmissions within 180 days and accounted for 77% of all readmissions. Age younger than 80 years (odds ratio, 1.14; 95% CI, 1.08–1.21), black race (odds ratio, 1.18; 95% CI, 1.10–1.26), and Medicare or Medicaid payor status (odds ratio, 1.21; 95% CI, 1.13–1.30; odds ratio, 1.34; 95% CI, 1.23–1.46, respectively) were associated with greater odds of 30-day readmission while female gender was associated with reduced odds (odds ratio, 0.92; 95% CI, 0.87–0.96). Comorbidities including malignancy (odds ratio, 1.34; 95% CI, 1.24–1.45), collagen vascular disease (odds ratio, 1.30; 95% CI, 1.15–1.46), chronic kidney disease (odds ratio, 1.24; 95% CI, 1.18–1.31), liver disease (odds ratio, 1.22; 95% CI, 1.11–1.34), congestive heart failure (odds ratio, 1.14; 95% CI, 1.08–1.19), lung disease (odds ratio, 1.12; 95% CI, 1.06–1.18), and diabetes (odds ratio, 1.12; 95% CI, 1.07–1.17) were associated with greater odds of 30-day readmission. Index hospitalization characteristics including longer length of stay, discharge to a care facility, higher hospital annual severe sepsis case volume, and higher hospital sepsis mortality rate were also positively associated with readmission rates. Conclusion: The 30-day and 180-day readmissions are common in sepsis survivors with significant resultant cost and mortality. Patient sociodemographics and comorbidities as well as index hospitalization characteristics are associated with 30-day readmission rates.